Using the 2006 PISA Questionaire to Evaluate the Measure of Educational Resources: A Rasch Measurement Approach - Ruixue Liu; Letao Sun; Jing Yuan; Kelly Bradley (International Journal of Assessment Tools in Education)
School educational resource is a key focus when studying school improvement due to its influence on learning outcomes.  Because of this, careful attention should be given to the way educational resource is operationalized and measured.  Using the 2006 PISA American sample containing 166 schools, this paper aims to validate the 13-item PISA School Educational Resource Scale with Rasch analysis.  Winsteps software was used in the analysis to evaluate how well the instrument measured the construct of school educational resource.  The results revealed that the PISA 2006 data gave an overall indication of good fit to the model despite the instrument did not separate respondents well.  In regards to the quality of items, the majority of items perform consistently with the model.  However, there are not enough items to discriminate the situation of school education resource for schools which are above the average educational resources.